Single-step fluorescence recognition of As3+, Nd3+ and Br− using pyrene-linked calix[4]arene: application to real samples, computational modelling and paper-based device. (7th December 2018) - Sutariya, Pinkesh G.; Soni, Heni; Gandhi, Sahaj A.; Pandya, Alok
Abstract : A new fluorescence sensor has been synthesized for its selective recognition of As 3+ (11.53 nM), Nd 3+ (0.65 nM) and Br − (11.25 nM). Abstract : A new fluorescence sensor, namely, TDPC, which is composed of a pyrene group connected to calix[4]arene as the fluorogenic unit, has been synthesized, characterized and analyzed with regard to its selective sensing ability for As 3+ (0–150 nM), Nd 3+ and Br − (0–120 nM), with detection limits of 11.53 nM, 0.65 nM and 11.25 nM, respectively. The binding constant ( K s ) was found to be 7.842 × 10 8 M −1 for As 3+, 6.877 × 10 8 M −1 for Nd 3+ and 6.311 × 10 8 M −1 for Br − . Furthermore, we report an easy-to-use, low-cost and disposable paper-based sensing device for rapid chemical screening of As 3+, Nd 3+ and Br − . The device comprises a luminescent sensing probe embedded in a cellulose matrix in which resonance energy transfer seems to be the sensing mechanism. It opens up new opportunities for simple and fast screening in remote settings where sophisticated instrumentation is not always available. The MOPAC2016 software package was used to optimize TDPC using the well-established PM7 method, and the HOMO–LUMO energy band gap was calculated for TDPC and TDPC with structures based on As 3+, Nd 3+ and Br − ions. To determine the influence of different metal ions on TDPC, a molecular docking study was carried out using HEX software. Furthermore, to assess its analytical applicability, the prepared sensor was successfully used for the analysis of two different real samples (an industrial soil sample for Nd 3+ and industrial waste water for As 3+ and Br − ) to validate the proposed method, with recoveries of ions of 95–99%.